Persistence of Pathological Distribution of NK Cells in HIV-Infected Patients with Prolonged Use of HAART and a Sustained Immune Response - Frias, Mario (PLoS One, 2015)
OBJECTIVE: A prospective analysis of the distribution of NK subsets and natural cytotoxicity receptors (NKp30/NKp46) in HIV patients with long-term HAART use and sustained virological and immunological response. METHODS: The main inclusion criteria were: at least 3 years’ receipt of HAART; current CD4(+) count ≥ 500 cells/mm(3); undetectable viral load for at least 24 months; no hepatotropic virus co-infection. Percentages of CD56(dim), CD56(bright) NK cells and CD56(neg) CD16(+) cells were obtained. Expression of the NCRs, NKp30 and NKp46 was analysed in CD56(+) cells. Thirty-nine infected patients and sixteen healthy donors were included in the study. RESULTS: The percentages of total CD56(+) and CD56(dim) NK cells were significantly lower in HIV-infected patients than in healthy donors (70.4 vs. 50.3 and 80.9 vs. 66.1 respectively). The percentage of total CD56(+) NK cells expressing NCR receptors was lower in HIV patients than in healthy donors (NKp30: 25.20 vs. 58.63; NKp46: 24.8 vs. 50.59). This was also observed for CD56(dim) and CD56(bright) NK cells. Length of time with undetectable HIV viral load was identified as an independent factor associated with higher expression of NKp30 and NKp46. CONCLUSION: Despite the prolonged and effective use of HAART, HIV-infected patients do not fully reconstitute the distribution of NK cells. Length of time with an undetectable viral load was related to greater recovery of NKp30/NKp46 receptors.